2001
DOI: 10.1086/324003
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Entecavir Treatment Results in Sustained Antiviral Efficacy and Prolonged Life Span in the Woodchuck Model of Chronic Hepatitis Infection

Abstract: Entecavir (ETV) is a guanosine nucleoside analogue with potent antiviral efficacy in woodchucks chronically infected with woodchuck hepatitis virus. To explore the consequences of prolonged virus suppression, woodchucks received ETV orally for 8 weeks and then weekly for 12 months. Of the 6 animals withdrawn from therapy and monitored for an additional 28 months, 3 had a sustained antiviral response and had no evidence of hepatocellular carcinoma (HCC). Of the 6 animals that continued on a weekly ETV regimen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 33 publications
3
81
1
Order By: Relevance
“…It is particularly refractory to current antiviral therapy, yet its elimination is a prerequisite for any real cure of an HBV infection. Although the half-life of preformed CCC DNA remains a hotly debated issue (21,33,40,43,44,58,70), effective, long-term antiviral treatment to block the synthesis of RC DNA, thus depleting the precursor to CCC DNA, can lead to significant reduction of CCC DNA in vitro and in vivo (1,3,8,11,18,22,49,64,69). These results indicate that continuous replenishment of the CCC DNA pool, via either de novo infection or intracellular amplification, is required to maintain persistent infections.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly refractory to current antiviral therapy, yet its elimination is a prerequisite for any real cure of an HBV infection. Although the half-life of preformed CCC DNA remains a hotly debated issue (21,33,40,43,44,58,70), effective, long-term antiviral treatment to block the synthesis of RC DNA, thus depleting the precursor to CCC DNA, can lead to significant reduction of CCC DNA in vitro and in vivo (1,3,8,11,18,22,49,64,69). These results indicate that continuous replenishment of the CCC DNA pool, via either de novo infection or intracellular amplification, is required to maintain persistent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several nucleos(t)ide analogues such as lamivudine [Dienstag et al, 1995], adefovir dipivoxil [Chin et al, 2001], and entecavir [Colonno et al, 2001] have been found to consistently produce rapid and dramatic decreases in viremia [Dienstag et al, 1995[Dienstag et al, , 1999Lai et al, 1998;Suzuki et al, 1999]. For the serological monitoring of chronic hepatitis patients under treatment with nucleos(t)ide analogues, improvement of alanine transaminase level, seroconversion from HBe antigen (HBeAg)-positive to anti-HBe antibody (HBeAb)-positive, and peripheral HBV DNA concentration are used as markers in chronic active hepatitis, and both HBeAg seroconversion and HBV DNA levels below the detection limit and/or of 10 5 copies/ml are commonly used as primary treatment endpoints [Lok et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…More potent antivirals, like entecavir (4,9), and multiple vaccinations of more than three injections could further enhance specific immune responses and yield better results.…”
mentioning
confidence: 99%